Chasing Respectability: Pro-Immigrant Organizations and the Reinforcement of Immigrant Racialization. (November 2022) - Brown, Hana E.; Jones, Jennifer A.
In this article, we investigate the role that pro-immigrant organizations play in immigrant racialization. Drawing on a critical case study from the longest standing immigrant rights organization in North Carolina, we demonstrate how immigrant rights organizations can racialize new Latinx arrivals even as they advocate for them. We interrogate the organization's multi-year, state-wide campaign to counteract mounting public characterizations of Latinx immigrants as drunk drivers. Analyzing a critical juncture in this campaign, we demonstrate how El Pueblo, in their effort to contest the mainstream racialization of Latinxs, unintentionally doubled down on that same racialization, buying into respectability politics and reinforcing derogatory stereotypes of Latinxs. We outline three central maneuvers that grounded this particular respectability politics campaign and demonstrate the utility of respectability politics as a framework for understanding organizational racialization processes. These findings suggest the need to shift focus toward community organizations as key sites of immigrant racialization and highlight the need for inquiry into the racialized assumptions of pro-immigrant forces.